2008
DOI: 10.1007/s12206-007-1204-5
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy MRAC controller design for vane-type air motor systems

Abstract: Air motors are widely used in the automation industry due to special requirements, such as spark-prohibited environments, the mining industry, chemical manufacturing plants, and so on. The purpose of this paper is to analyze the behavior of a vane-type air motor and to design a model reference adaptive control (MRAC) with a fuzzy friction compensation controller. It has been noted that the rotational speed of the air motor is closely related to the compressed air's pressure and flow rate, and due to the compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…As a result, conventional PID feedback controllers [1,2] are not so effective even for position control. There have been a number of investigations and analyses of the dynamics of vane-type air motors [2][3][4][5] carried out to date, most for different types of control, like PID control [2], MRAC [3], and sliding mode control [5]. In * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, conventional PID feedback controllers [1,2] are not so effective even for position control. There have been a number of investigations and analyses of the dynamics of vane-type air motors [2][3][4][5] carried out to date, most for different types of control, like PID control [2], MRAC [3], and sliding mode control [5]. In * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…The air pressure entering the air motor will decrease in a non-regular fashion due to the various volumes of the two vanes. To counteract these uncertain behaviors and eliminate the dead zone caused by friction, modelreferencing adaptive control (MRAC) with fuzzy control [3] proposed. Fuzzy rules combined with sliding mode control are used in the aforementioned study [5] to improve the steady response and build robustness with an air motor ball screw table.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with passive suspension systems, fully active suspension systems provide improved performance over a wide range of frequencies. Hence, it has been studied by various researchers [1,3,[11][12][13][14][15][16][17][18]. However, fully active suspension systems have the disadvantages of complexity, high cost and high-energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…In the defuzzification process, these results are used to calculate the physical control inputs, such as voltages, currents, and so on. In [13], the mode reference adaptive control (MRAC) is proposed with fuzzy control to eliminate the dead-zone caused by friction in an air motor system. The experimental results showed that the MRAC could be tracked and that an accurate speed control performance was attainable.…”
Section: Introductionmentioning
confidence: 99%